Delay perturbed state-dependent sweeping process. Issue 2 (1st February 2016) - Haddad, Tahar; Haddad, Touma
Abstract : In this paper, we prove a result on the existence of solutions of a differential inclusion governed by a class of nonconvex state-dependent sweeping process with perturbation depending on all the variables and with delay. The moving set involved in the process is prox-regular and depends both on the time and on the state.